2016
DOI: 10.1186/s40035-016-0069-x
|View full text |Cite
|
Sign up to set email alerts
|

Stroke-like onset of brain stem degeneration presents with unique MRI sign and heterozygous NMNAT2 variant: a case report

Abstract: BackgroundAcute-onset neurodegenerative diseases in older patients are rare clinical cases, especially when the degeneration only affects specific regions of the nervous system. Several neurological disorders have been described in which the degeneration of brain parenchyma originates from and/or primarily affects the brain stem. Clinical diagnosis in these patients, however, is often complicated due to a poor understanding of these diseases and their underlying mechanisms.Case presentationIn this manuscript w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 19 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…10 A heterozygous NMNAT2 variant was shown by whole-exome sequencing in a patient who presented with a stroke-like event followed by progressive brainstem degeneration. 52 The axonal death program has also been linked to susceptibility to amyotrophic lateral sclerosis (ALS). For example, studies in patients with ALS have identified SARM1 variant alleles that alter the SARM1 autoinhibitory domain and constitutively hyperactivate SARM1 NADase activity.…”
Section: Clinical Correlationsmentioning
confidence: 99%
“…10 A heterozygous NMNAT2 variant was shown by whole-exome sequencing in a patient who presented with a stroke-like event followed by progressive brainstem degeneration. 52 The axonal death program has also been linked to susceptibility to amyotrophic lateral sclerosis (ALS). For example, studies in patients with ALS have identified SARM1 variant alleles that alter the SARM1 autoinhibitory domain and constitutively hyperactivate SARM1 NADase activity.…”
Section: Clinical Correlationsmentioning
confidence: 99%